Hospital Savings Association : inter-departmental correspondence - Smyth, J. L.
1932-10-06 1932 1930s 2 pages I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From Mr. J.L. Smyth Department Social Insurance. To Mr. Walter M. Citrine. Date 6th October, 1932. SUBJECT. HOSPITAL SAVINGS ASSOCIATION. The Hospital Savings Association came into existence following the report of the Cave Committee, which recommended that the voluntary system of financing hospitals should be preserved. The Savings Association consists of groups of workers who contribute 3d. a week which is remitted to the Association by Group Secretaries. Membership is limited to the hospital income limit which is £4 per week for a single man or woman, £5 per week if without children under 16, and £6 per week if married with children under 16. People whose income is above those limits do not come into the scheme but may be voluntary contributors, for which they receive certain privileges. The Savings Association scheme is briefly that the contributor presents a card at any hospital connected with the scheme and receives treatment without payment, the bill being paid by the Association. If the hospital is not on the list then the contributor pays the account and gets a refund from the Association. There are advantages also in regard to optical and dental benefit and certain dependants of the contributors are covered by the whole scheme in addition to the contributor himself. The Annual Meeting of the Association is attended by the Group Secretaries, and there are about 2,000 of these. The organisation is growing very rapidly. In 1924 there were approximately 62,000 contributors and the amount paid in was about £22,000, whilst in 1931 over 900,000 persons paid more than £500,000. The Chairman is Sir Alan Anderson, whose mother was Elisabeth Garratt Anderson [Elizabeth Garrett Anderson], the first woman doctor in this country. The Prince of Wales is a patron, and the Vice-Presidents include Lord Dawson, Lord Moynhan, W.A. Appleton, J.H. Thomas, and Sir Arthur Stanley. The Executive is composed of hospital members, contributor members, and general members. Mr. Henry Lesser of the Gas Light & Coke Company and Mr. Stanley L. Duff, who is a prominent member in the Friendly Societies movement, are both members of the Executive. Neither of them are sympathetic to our point of view on social services. There is nobody on the Executive so far as I can see who has any connection with our Movement. At the last Annual Meeting Mr. C.G. Ammon gave an address in which he praised the work being done, which he compared to the Brotherhood Movement. Mr. Ammon took the place of Sir Robert Horne who was to have given the address. The year before last Mr. Alexander of the Co-operative Society gave an address. 292/842/1/2